PELATIHAN KEWIRAUSAHAAN MEMBUAT PROPOSAL BISNIS DAN PICK DECK UNTUK MENARIK MINAT INVESTOR - syafril, syafril; sofia, sofia; mohdari, mohdari; Fahmi, Muhammad; Fadilah, Neti Rosiana (PT. Karya Inovatif Nusantara, 2025)
Entrepreneurship training, including creating business proposals and pitch decks to attract investors, is an activity required of lecturers to fulfill the Tri Dharma of Higher Education. This training serves as a transfer of knowledge relevant to their field of study and duties as lecturers. This business proposal and pitch deck training is expected to equip participants with the skills to properly start a business, thereby ensuring its continued growth and attracting investors. This training is a collaboration between the UPKK UIN Antasari Banjarmasin and practitioners and professionals in their respective fields, providing useful and easily applicable materials to participants. The results of this training are expected to provide knowledge and share experiences with participants.